Study the Stability of Pedestrian Floating Bridges under the Hydrodynamic Effects Case Study (Pedestrian Bridge Between Tartus and Arwad Island) - الخطيب, حسن; عصام ناصر; عدنان ابراهيم (Latakia University Journal -Engineering Sciences Series, 2022)
The forces supporting the pontoon bridge in the vertical direction are the buoyant forces, while the mooring system (cables) or the shape of the bridge supports the bridge in the horizontal direction. The primary loads acting on a pontoon bridge are the environmental loads that are due to the random influence of wave and wind forces it will be difficult to predict the exact value and direction of the correct loading of the bridge. The response of the bridge will be defined by the bending stiffness, the bridge mass, the rotational accelerations, and the stiffness of the pontoon joints if separate pontoons are used. The main objective of the research is to conduct a general review of the existing floating bridges, in order to choose a specific model for the floating bridge that will connect the city of Tartous with the island of Arwad, and to clarify the modeling and arithmetic procedures for one raft under the influence of a self-weight load and under the influence of a live load, and then a simplified model of the total model of the bridge will be built. With a single girder consisting of a metal beam that rests on two rafts with different spacings (30m-40m-50m) and showing stability under the influence of wave loads and calculating the longitudinal and transverse rotational accelerations, which is an important criterion for the comfort and safety of bridge users. Where the results showed the stability and stability of the raft under the influence of its own weight load, pedestrian load and wave load with a height of 2 meters at the lanes (30m-40m-50m) And we will notice the stability and stability of the metallic perimeter also under the influence of the self-weight load and the pedestrian load, to note after that when the corridor is increased to more than 55m the metal bridge over the two pontoons will collapse.